Banking Risk in Selected MENA Countries - Gadou, Lamya M A (International Journal of Innovative Research and Scientific Studies, 2022)
This study examines the influence of bank-specific variables on the individual risk of 58 banks in ten MENA countries over the period 2011-2019. Firstly, investigating the correlations among the banks’ stock returns depicts that the banks with the highest correlations are in Saudi Arabia, the United Arab Emirates, and Qatar, either domestically or across countries. Then, the individual bank risk ranking for the entire sample based on estimated historical Value-at-Risk (VaR) and Estimated Shortfall (ES) shows that the corresponding positions of banks according to their riskiness differ slightly. Noticeably, the National Bank of Fujairah in the United Arab Emirates has the highest idiosyncratic risk level in terms of both risk measures. We lastly conducted fixed and random effects panel regression models to examine the impact of bank-specific balance sheet data and macroeconomic variables on bank risk levels captured by VaR and ES. The whole sample comprises publicly listed banks in 10 countries, which were further divided into 2 sub-samples for the Gulf Cooperation Council (GCC) region and Mediterranean Partner Countries (MPCs). The outcomes of the aggregate sample suggest that lower leverage, profitability, and economic growth may exacerbate idiosyncratic risk. Results also demonstrate that strengthening stability and regulatory capital positions would lower banking risk. Considering the GCC sub-sample for VaR and ES models, we found that both risk measures typically increase with greater liquidity.